What makes a city 'smart'?. (December 2016) - Thompson, Emine Mine
Taking advantage of information and communications technology tools and techniques for city administration, whether it is for urban planning activities, for transport solutions or many other purposes, is not a new concept. However, in order for a city to be classified as 'smart', a synthesis of intelligence that transcends mere utilisation is essential. This article analyses the increasing use of information and communications technology and sensing technologies in cities by examining this new way of city governing from a critical perspective. Existing projects and initiatives were investigated to find out how, and to what extent, these tools are being employed by cities. The advantages and the current shortcomings of smart city are also discussed in order to understand the viability of using these tools.